Adolescent Identity Status and Socio-Demographic Factors: A Cross-Sectional Study Using the Three-Dimensional Model - Keksi Girindra Swasti; Budi Anna Keliat; Yossie Susanti Eka Putri; Widyatuti Widyatuti (An Idea Health Journal, 2026)
Background: Identity formation represents a key aspect of psychosocial development during adolescence. In the three- dimensional model, identity comprises commitment, in-depth Methods: A descriptive analysis design with a cross-sectional approach was employed. Sample selection was conducted in two stages using cluster and purposive sampling methods. Results: Adolescent identity was assessed using the Utrecht Management of Identity Commitments Scale. The association between socio-demographic factors and adolescent identity status was analyzed using the Chi-square test. The findings indicate that adolescents demonstrated high commitment, moderate in-depth exploration, and low reconsideration of commitment. Most adolescents were in a moratorium stage, while a smaller proportion had achieved identity status. Conclusion: Identity status was influenced by gender, family type, maternal employment status, and school location. These findings suggest that adolescent commitment remains malleable.